Pengaruh Aktivator Effective Microorganism 4 Terhadap Proses Pembuatan Pupuk Organik dari Kotoran Sapi - Sri Wahyu Murni; Tunjung Wahyu Widayati; Bassmall Andriouty Pratama; Satriyo Oktavianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Cow's excrements originated from slaughterhouse is an organic waste that can damage the environmenttherefore need to be process to make something such as fertilizer using activators that help thedecomposition process run faster. Activator used in this experiment is Effective Microorganism 4.Decomposition of cow’s excrements becoming organic fertilizer by mixing cow’s excrements with EffectiveMicroorganism 4 activator. Ratio of cow’s excrements weight (Metric Ton) by volume (Liter) of EffectiveMicroorganism 4 activator is 1:0; 1:1; 1:2; 1:3; 1:4. Thereafter, add the anorganic fertilizer (Urea, KCl,SP-36) and limestone to the mixture each about 2,5 kilograms after that cover the mixture with plastic wrapand make some holes with bamboo. The experiment result for this study using Effective Microorganism 4activator by adding 4 liter in the decomposition process for 18-21 days to produce organic fertilizer consistabout 15,01% organic carbon, 0,87% total nitrogen, 17,25 C/N ratio. These result meet the qualitystandards set by the Minister of Agriculture No.70/Permentan/SR.140/10/2011.